(untitled) (Chest & Heart Journal, 2021)
Background & Objective: Diagnosis of tuberculosis (TB) is not always easy, particularly if it is a case of smear-negative pulmonary tuberculosis (SNPTB). Patients with respiratory symptoms resembling SNPTB is difficult to differentiate on the basis of clinical features, X-ray chest and Xpert MTB/RIF negativity. So additional diagnostic tests with high sensitivity and specificity is needed to increase the yield of the ongoing diagnostic strategy for SNPTB. That purpose the present study tested the value of serum adenosine deaminase (ADA) as an adjunct to the existing diagnostic aids. Patients & Methods: The present cross-sectional analytical study was carried out in the Department of Respiratory Medicine, National Institute of Diseases of the Chest & Hospital (NIDCH), Mohakhali, Dhaka over a period of one year from April 2018 to March 2019. Patients attending in the above-mentioned hospital with respiratory ailments and were suspected of having pulmonary tuberculosis from their clinical presentation, chest radiography, sputum smear and Xpert MTB/RIF negativity were the study population. A total of 60 such patients (suspected SNPTB), 30 smear-positive pulmonary tuberculosis (SPPTB) cases and 30 healthy controls were included in the study. According to National Guidelines for Management of Tuberculosis, if a patient with symptoms suggestive of TB with two consecutive sputum specimens being negative for AFB, Xpert MTB/RIF negative, chest X-ray abnormalities consistent with active TB and the diagnosis was made by a qualified physician, the case was considered as having SNPTB. Result: The SNPTB patients had a moderate rise of serum ADA (35.4 U/L) compared to the SPPTB patients who had the highest serum ADA and the healthy controls who had the lowest serum ADA (41.1 ± 11.8 vs. 22.7 ± 5.5 U/L respectively). In order to find a cut-off value for serum ADA at which it is fairly sensitive and specific to diagnose SNPTB, a receiver-operating characteristic (ROC) curve was constructed with an area under the curve being 0.851(95% CI = 0.745-0.957, p < 0.001). The ROC curve gave a cut-off value 27.5 U/L at which the serum ADA had a sensitivity, specificity, PPV, NPV and the diagnostic accuracy of 80, 80, 88.9, 66.7 and 80% respectively. The LR+ and LR- were 4.0 and 0.25 respectively. Conclusion: From the findings of the study, it can be concluded that the serum ADA has a modest sensitivity and specificity in the diagnosis of SNPTB. However, the results of ADA assays should be interpreted in conjunction with clinical presentations and other laboratory test findings. As the LR+ is only 4, the test is of little clinically useful in the diagnosis of SNPTB. Therefore, estimating ADA levels should not be a valuable additional test, in the rapid diagnosis of SNPTB patients provided a large-scale study on a cross-section of diverse SNPTB population to confirm its limited usefulness. Chest Heart J. 2020; 44(1) : 34-42